Drug Sensitivity Pattern in Children with Blood Culture Positive Enteric Fever in a Tertiary Care Hospital in Pakistan - Kaleem Ur Rahman, Syed; Halim, Alia; Hayat, Mohsin; Rashid, Sannah; Malik, Munir Iqbal (Infectious Diseases Journal of Pakistan, 2023)
Background: Salmonella infections are endemic in Pakistan and resistance to these infections is increasing which has implications. We aim this study to determine the antimicrobial resistance pattern of Salmonella infections among children admitted at tertiary care hospital in Pakistan. Methods: We have performed an audit in children aged 1 month to15 years with positive blood culture for Salmonella enterica serovars Typhi and Paratyphi A, diagnosed at Shifa international hospital’s Microbiology Laboratory, from May 2012 to Dec 2013. Blood cultures positive for S. Typhi and S. paratyphi A isolates were confirmed with specific anti-sera and their antibiogram determined by Modified Kirby-Bauer Disc Diffusion method using 6 relevant antibiotics (Ampicillin, Trimethoprimsulphamethoxazole, Chloramphenicol, Ciprofloxacin, Cefixime and Ceftriaxone). Interpretation was done according to the guidelines of Clinical and Laboratory Standards Institute. Results: In our study we had 200 positive cultures, 75% were Salmonella typhi and 25% were Salmonella paratyphi A isolates. Overall mean age of children was 8.1 +S.D=4.3 years. Majority (61%) were males. Of the total isolates, 88% were resistant to one or more drugs with 75% and 25% being serotype typhi and paratyphi A respectively. Resistance to 1st line antibiotics was significant in Salmonella Typhi compared to Salmonella paratyphi A (co-trimoxazole 63% vs. 6%, Chloramphenicol 71% vs 14%, Ampicillin 67% vs 10%). MDR strains were also more common in Salmonella Typhi (59%) as compared to Salmonella Paratyphi (20%). Conclusions: The study showed significant resistance to 1st line antibiotics by Salmonella serotype typhi compared to Salmonella serotype Paratyphi A. Parenterally and orally administered third generation cephalosporins remain effective drugs against infections caused by Salmonella serotype typhi and Paratyphi A. Key Words: Enteric fever, Drug resistance, Children